Studies on Impedance and Dielectric Properties of Bi2/3Cu3Ti4−xSi xO12 (x = 0.05 and 0.1) Ceramics Synthesized by the Semi-wet Method - Rai V.S.; Prajapati D.; Kumar V.; Verma H.; Upadhyay S.; Verma M.K.; Kumar A.; Singh N.B.; Mandal K.D. (My University, 2025)
The ceramic material Bi2/3Cu3Ti4−xSixO12 (where x = 0.05, and 0.1) with complex perovskite structure was prepared by semi-wet method sintered at 1173 K for 8 h. X-ray diffraction studies proved the single phase pattern of ceramics. The ceramics were further characterized by SEM and EDX for the microstructural properties and elemental analysis, respectively. The average grain sizes of BCTSO-0.05 and BCTSO-0.1 ceramics were found to be 0.32, and 0.47 μm, respectively. The value of dielectric constant for the BCTSO-0.05 and BCTSO-0.1 ceramics were measured as 953 and 1316 at 100 Hz and 503 K. The tangent loss values of BCTSO-0.05 and BCTSO-0.1 ceramics were found 0.08 and 0.06, respectively, at 303 K and 10 kHz. The oxidation states of the constituent elements in the BCTSO-0.1 ceramic, were verified by XPS. The Impedance and Modulus studies illustrate that the Maxwell–Wagner type of relaxation phenomena is exhibited in the ceramics. The variation of conductivity as function of inverse of absolute temperature is governed by the Arrhenius equation, in the temperature region of 303 to 503 K. © ASM International 2023.